Disocrse Analysis of Figurative Language in the Poems “A Madrigal and Bridal Song” by William Shakespeare - Brusly Watson Kelmaskosu; Piter Titirloloby; Saleman Hartoyo (Journal Innovation In Education, 2024)
Figure of speech is used to beautify literary work especially poetry. Figurative language can make the poetry exciting and unique. The Objectives of this research are to identify the kinds of figurative language used in “A Madrigal” and “Bridal Song” poems by William Shakespeare and identify how are the Macrostructure, Microstructure and Superstructure of the language realized in “A Madrigal” and “Bridal Song” poems by William Shakespeare. The type of this research is a qualitative research used descriptive method. The result of the research show that A Madrigal and Bridal Song use figurative language to express the idea or think of William Shakespeare. The researcher find out 5 kinds of figurative language in A Madrigal poem by William Shakespeare. The kinds of figurative language in A Madrigal poem are Metaphor have 22 figurative language, Simile have 4 figurative language, symbolism have 3 figurative language parallelism have 15 figurative language, antithesis have 2 figurative language. Researcher found the dominant figurative language in a Madrigal Poem is Metaphor. There are 3 kinds of figurative language in Bridal Song poem by William Shakespeare. The researcher found 3 kinds of figurative language there are Parallelism has 5 figurative language, metaphor has 9 figurative language, and symbolism has 7 figurative language.